Digital pamphlet of Domestic Tourism based on Augmented Reality: The Promotion of Sidoarjo Urban Tourism Site - Dijaya, Rohman; Suprayitno, Eko Agus (International Journal of Engineering and Technology, 2018)
Sidoarjo has the potential of historic sights of the world and the center of art heritage in East Java Indonesia. Augmented reality (AR) is being developed as an intelligent tourism promotion to provide information about real destinations and attractions from tourist attractions. Its use will maximize the satisfaction of tourists based on the active use of tourists. Several historic buildings in some areas of eastern Java have been almost recreated. We have taken advantage of the typical ethnic building of the town square to represent the board game. This study presents a new digital pamphlet of domestic tourism based on added facts. Through AR, this historic building generates new life, giving visitors a more engaging and interactive experience that further educates them about the temple itself and about the different historical periods in which the reliefs are carved. Augmented reality, combined with audio commentary in multiple languages, will help visitors to find different reliefs more easily and appreciate the true wonders of this site and the motives behind the historic building carvings.